Left Main Coronary Artery Compression in Pulmonary Arterial Hypertension. (1st December 2015) - Albadri, Kadhem; Jensen, Jesper M.; Christiansen, Evald H.; Mellemkjær, Søren; Nielsen‐Kudsk, Jens Erik
Abstract : In patients with pulmonary arterial hypertension (PAH), chest pain is most likely due to right ventricular demand ischemia. We report a patient with idiopathic PAH who developed severe angina due to extrinsic compression of the left main coronary artery (LMCA) from a dilated pulmonary artery trunk. The diagnosis was verified by electrocardiogram after exercise, coronary angiography including intravascular ultrasound, and cardiac multidetector computed tomography (MDCT). The origin of the LMCA was high in the left coronary sinus, facilitating extrinsic compression. The patient was successfully treated by percutaneous coronary intervention with stent implantation in the LMCA. Extrinsic compression of the LMCA is a severe and potentially fatal complication that should be considered in all patients with PAH and angina. MDCT is the method of choice for first‐line diagnosis.